Immunoexpression of CDX2 in metastatic nonintestinal adenocarcinomas: an immunohistochemical pitfall and its pathological implications - Krachi Agarwal; Preeti Agarwal; Shipra Singh; Mili Jain; Sumaira Qayoom (Surgical and Experimental Pathology, 2023)
Abstract Background CDX2, a homeobox gene is the marker of intestinal differentiation. Its expression may lead to misdiagnosis while evaluating metastasis from unknown primary. In the present narrative, we discuss the clinical, morphological, and immunohistochemical (IHC) findings of metastatic adenocarcinoma of the lymph node that displayed nuclear immunoexpression of CDX2. However, the clinical and radiological picture supported the non-intestinal primary; prostate in one and lung in the other. Case presentation A 68-year-old man presented cervical lymph node enlargement. An epithelial tumor with acinar and cribriform pattern was seen that showed expression of CK, CDX2, and PSA in IHC. The patients complained of nonspecific symptoms related to both the gastrointestinal system and the prostate. Serum PSA was diagnostic (> 500 ng/ml). Similarly, core biopsy from mediastinal lymph node from a 51-year-male was received with possible differential of cancer and tuberculosis. Moderately differentiated adenocarcinoma was observed with the expression of EMA, CK 7, CDX2, and TTF1. The expression of both CDX2 and TTF1 was patchy. When the patient was called and all the details were sought the computed tomography (CT) thorax showed a lower chest wall lesion and multiple metastasis. The case was hence signed off as primary from lung on basis of clinical picture. Conclusion Such deviants must be reported and recorded. The knowledge of these will make a pathologist cautious and thus avoid misdiagnosis.